2014
DOI: 10.1158/1055-9965.epi-13-0944
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives and Breast Cancer Risk Overall and by Molecular Subtype Among Young Women

Abstract: Background Evidence suggests that recent oral contraceptive (OC) use is associated with a small increased breast cancer risk; yet risks associated with contemporary OC preparations and by molecular subtype are not well characterized. Methods We conducted a population-based case-control study of invasive breast cancer among women ages 20-44 residing in the Seattle-Puget Sound area from 2004-2010 (985 cases and 882 controls). We collected information on contraceptive use and participant characteristics via an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 49 publications
5
81
2
3
Order By: Relevance
“…In addition, in our study, the oral contraceptive use demonstrated a protective action, different from what has been described in the literature (30,31).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, in our study, the oral contraceptive use demonstrated a protective action, different from what has been described in the literature (30,31).…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is in agreement with other works reporting the increased risk of breast cancer among women who consume oral contraceptive [47], [48]. Our observation suggests that the hormonal status and the genico-obstetric history of patients are important to direct miRs expression as potential prognostic biomarkers to predict some clinical features.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, Dolle et al (20), Beaber et al (18) and Kwan et al (23) reported that OC use increases the risk of TNBC; however, Marchbanks et al (29), Kawai et al (25) and Kabat et al (22) did not confirm this association.…”
Section: Discussionmentioning
confidence: 98%